SILVICULTURE OF NATURAL REGENERATION STAND OF Calycophyllum spruceanum (Benth.) Hook. f. ex K. Schum (RUBIACEAE) IN ALLUVIAL FLOODPLAIN OF IQUITOS, PERUVIAN AMAZON - FREITAS-ALVARADO, Luis (2021)
Horizontal structure and silvicultural conditions of a naturally-regenerated Calycophyllum spruceanum (known in Peru as “Capirona”) stand in an alluvial floodplain were assessed. A forestry inventory was carried out and silvicultural conditions parameters were measured according their size categories. C. spruceanum stand has 961 individuals, 7.68m2 of basal area and 25.68m3 of volume. Silvicultural condition by crown lighting indicated that 40.48% of total population has deficient lighting and belongs to the latizales class. This deficient lighting also affected the crown shape because 33.51% of the stand belong to the “tolerable” class with half-crown circle and 22.27% varies from poor to very poor crown. Regarding the stem quality, 30.07% of individuals shows well straight and cylindrical stems and 25.7% with straight stems in higher of its length. The silvicultural analysis of the stand shows that there are a high number of plants with poor lighting and crown shape, so it is considered that the appropriate silvicultural treatment is a thinning of the selective-chosen type in order to regulate the distance between the best shaped plants and vigorous and improve the conditions for their development.